2017
DOI: 10.4049/jimmunol.1601433
|View full text |Cite
|
Sign up to set email alerts
|

Normal Thymocyte Egress, T Cell Trafficking, and CD4+ T Cell Homeostasis Require Interactions between RGS Proteins and Gαi2

Abstract: Adaptive immunity depends upon mature thymocytes leaving the thymus to enter the bloodstream and the trafficking of T cells through lymphoid organs. Both of these requires heterotrimeric Gαi protein signaling, whose intensity and duration are controlled by RGS proteins. Here, we show that RGS protein/Gαi2 interactions are essential for normal thymocyte egress, T cell trafficking, and homeostasis. Mature thymocytes with a Gαi2 mutation that disables RGS protein binding accumulated in the perivascular channels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…RGS proteins decrease the activity of G proteins by accelerating GTP hydrolysis and, thereby, accelerate G protein inactivation but also its activation [ 56 58 ], which appears to be essential for chemotaxis [ 8 , 37 ]. It was shown that immune cells, harboring the Gα i2 G184S mutant, which causes resistance to RGS proteins, exhibit major alteration in chemotaxis [ 8 ]. The active state of the G184S Gα i2 mutant is prolonged, a condition mimicking the effects of SseI that persistently activates G i proteins.…”
Section: Discussionmentioning
confidence: 99%
“…RGS proteins decrease the activity of G proteins by accelerating GTP hydrolysis and, thereby, accelerate G protein inactivation but also its activation [ 56 58 ], which appears to be essential for chemotaxis [ 8 , 37 ]. It was shown that immune cells, harboring the Gα i2 G184S mutant, which causes resistance to RGS proteins, exhibit major alteration in chemotaxis [ 8 ]. The active state of the G184S Gα i2 mutant is prolonged, a condition mimicking the effects of SseI that persistently activates G i proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Third, following ligand exposure the effective concentration of heterotrimeric Gαi2 available for GPCR activation declines. This can adversely affect the kinetics of the signal transduction pathways (Hwang et al, 2017). Cells including neutrophils that lack an individual RGS protein typically exhibit enhanced GPCR signaling (Balenga et al, 2014;Chan et al, 2018;Kehrl, 2016;Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Cells including neutrophils that lack an individual RGS protein typically exhibit enhanced GPCR signaling (Balenga et al, 2014;Chan et al, 2018;Kehrl, 2016;Xie et al, 2016). Furthermore, studies of the G184S mice have largely reported augmented GPCR-linked Gαi signaling (Neubig, 2015), yet past studies examining leukocyte chemoattractant receptors have largely reported diminished signaling (Cho et al, 2012;Hwang et al, 2015;Hwang et al, 2017). In the present study, we found that neutrophils, which carry the Gαi2 G184S mutation exhibit a complex phenotype with features of both hyperactive and hypoactive Gαi signaling, which overlap with the phenotypes noted with Gαi gain-or a loss-of function mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotaxis assays were performed using a transwell chamber (Costar) as previously described ( 21 ). Where indicated the murine microvascular SVEC4-10EE2 endothelial cell line cells were cultured on the transwell insert until 90% confluence prior to use in the assay.…”
Section: Methodsmentioning
confidence: 99%